Strategy, diplomacy, humanity : life and work of Sahabzada Yaqub-Khan - Khan, Sahabzada Yaqub; Dil, Anwar S. (Islamabad ; San Diego : International Forum Takshila Research University, 2005)
Lectures of an ex-Foreign Minister of Pakistan; includes his brief life sketch.
Includes bibliographical references and index.
Keywords: Pakistan -- Foreign relations